Rain Man Unmasked: An ‘Escape’ of Language from the Left Hemisphere Unlocks Working Memory for Numbers - Klichowski, Michał (EC Psychology and Psychiatry, 2017)
The engagement of working memory by numbers can lead to a “temporary escape of language” from the left hemisphere. Thus, numbers can in a sense block the “smooth” processing of language. This finding sheds a new light on abilities of mathematical savants, like Raymond Babbitt from Rain Man, with exceptional counting skills but poor language command. Mathematical savants’ language is not “smooth” and rather limited to single word utterances. This is probably why all resources of their working memory (located in the left hemisphere) can be devoted to such exceptional counting.
Keywords: representations of numbers; representations of language; working memory; lateralization; mathematical savants; Rain Man